Stainless steels for general purposes – Part 2: Corrosion-resistant semi-finished products, bars, rods and sections (First revision) (ISO 16143-2:2004, MOD) - Maleque, Md. Abdul; Mat Jusoh, Ahmad Haziq; Salehudin, Nabilah Farhana; Yee, Sen Tat; Din, Mohd Idrus; Adenan, Rashimah; Abdullah, Mohamad Akhir; Mat Zain, Mohd Hafizy; Lim, Sooi San; Chum, Pak Kuan; Ahmad Salman, Shafiq Wazzan; Yazid, Zurawati; et al. (Department of Standard Malaysia (DSM), 2023)
This Malaysian Standard specifies the technical delivery conditions for semi-finished products, hot formed bars, rods, and sections for general purposes made of the most important corrosion-resistant stainless steel grades.